Astaxanthin-Shifted Gut Microbiota Is Associated with Inflammation and Metabolic Homeostasis in Mice. Issue 10 (18th August 2020) - Wu, Lei; Lyu, Yi; Srinivasagan, Ramkumar; Wu, Jinlong; Ojo, Babajide; Tang, Minghua; El-Rassi, Guadalupe Davilla; Metzinger, Katherine; Smith, Brenda J; Lucas, Edralin A; Clarke, Stephen L; Chowanadisai, Winyoo; et al.
ABSTRACT: Background: Astaxanthin is a red lipophilic carotenoid that is often undetectable in human plasma due to the limited supply in typical Western diets. Despite its presence at lower than detectable concentrations, previous clinical feeding studies have reported that astaxanthin exhibits potent antioxidant properties. Objective: We examined astaxanthin accumulation and its effects on gut microbiota, inflammation, and whole-body metabolic homeostasis in wild-type C57BL/6 J (WT) and β-carotene oxygenase 2 (BCO2) knockout (KO) mice. Methods: Six-wk-old male and female BCO2 KO and WT mice were provided with either nonpurified AIN93M (e.g., control diet) or the control diet supplemented with 0.04% astaxanthin (wt/wt) ad libitum for 8 wk. Whole-body energy expenditure was measured by indirect calorimetry. Feces were collected from individual mice for short-chain fatty acid assessment. Hepatic astaxanthin concentrations and liver metabolic markers, cecal gut microbiota profiling, inflammation markers in colonic lamina propria, and plasma samples were assessed. Data were analyzed by 3-way ANOVA followed by Tukey's post hoc analysis. Results: BCO2 KO but not WT mice fed astaxanthin had ∼10-fold more of this compound in liver than controls ( P < 0.05). In terms of the microbiota composition, deletion of BCO2 was associated with a significantly increased abundance of Mucispirillum schaedleri in mice regardless of gender. In addition to more liver astaxanthin in male KO compared with WT mice fed astaxanthin, the abundance of gut Akkermansia muciniphila was 385% greater, plasma glucagon-like peptide 1 was 27% greater, plasma glucagon and IL-1β were 53% and 30% lower, respectively, and colon NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activation was 23% lower (all P < 0.05) in male KO mice than the WT mice. Conclusions: Astaxanthin affects the gut microbiota composition in both genders, but the association with reductions in local and systemic inflammation, oxidative stress, and improvement of metabolic homeostasis only occurs in male mice.